1995
DOI: 10.1111/j.1469-8137.1995.tb01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of tomato to different carbon dioxide concentrations. Relationships between biochemistry and gas exchange during leaf development

Abstract: Tomato plants were transferred to diflerent CO,^ mole fraction.s (3.S(), 700, lCSO and 1400//mol CO.^ mol ') 31 d after sowing (2 "" of full expansion) and the light saturated rate of photosynthesis (P",^^) of the unshaded .Sth leaf was measured at either an ambient CO^ mole fraction, C\ of 350/miol CO^ mol " [P^^^^ (350)] or at the mole fraction of CO,^ at which the plants were grown. At 60 "" and 95 "o leaf expansion, P^^^ of high CO^ grown plants measured at growth CO^, was greater than the P^^,, (350) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The response of A to elevated (Table 1), This was observed in previous studies (Besford et al 1990a;Woodrow 1994a) and may be related to the sink activity of the plant (Hicklenton & Jollife 1980;Porter & Grodzinski 1984;Peet, Huber & Patterson 1986). The Rubisco activity followed a similar patterti to A (350) during leaf development, and was more affected as the growth CO. increased (Tables 1 & 2), A similar effect of varying growth CO, on Rubisco activities has been observed with cotton (Wong 1979) and rice (Rowland-Bamford et al 1991) but not with soybean (Campbell, Allen & Bowes 1988), However, the CO2 growth concentrations ranged from 160 to 900/imol CO2mor' in these last two studies, A major factor associated with the fall in A measured in 350Aimol CO2 mol' appears to be the loss of Rubisco activity and protein, since A was close to that predicted from the amount and kinetics of Rubisco in plants grown in either ambient or elevated CO2 concentrations (Besford 1990;Besford et al 1990a;Van Oosten, Wilkins & Besford 1995).…”
Section: Discussionmentioning
confidence: 81%
“…The response of A to elevated (Table 1), This was observed in previous studies (Besford et al 1990a;Woodrow 1994a) and may be related to the sink activity of the plant (Hicklenton & Jollife 1980;Porter & Grodzinski 1984;Peet, Huber & Patterson 1986). The Rubisco activity followed a similar patterti to A (350) during leaf development, and was more affected as the growth CO. increased (Tables 1 & 2), A similar effect of varying growth CO, on Rubisco activities has been observed with cotton (Wong 1979) and rice (Rowland-Bamford et al 1991) but not with soybean (Campbell, Allen & Bowes 1988), However, the CO2 growth concentrations ranged from 160 to 900/imol CO2mor' in these last two studies, A major factor associated with the fall in A measured in 350Aimol CO2 mol' appears to be the loss of Rubisco activity and protein, since A was close to that predicted from the amount and kinetics of Rubisco in plants grown in either ambient or elevated CO2 concentrations (Besford 1990;Besford et al 1990a;Van Oosten, Wilkins & Besford 1995).…”
Section: Discussionmentioning
confidence: 81%
“…Besford (1993) reported that the photosynthetic rate of plants grown at 1000 μmol·mol . This photosynthetic reduction is known to involve acclimation to elevated CO 2 for a long time (Besford et al, 1990;van Oosten et al, 1995;Yelle et al, 1990). However, no reduction of the maximum photosynthetic rate by elevated CO 2 and fogging was observed in this experiment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that the rate of photosynthesis is highly dependent on developmental stages and the response to CO 2 varies with the stage of development (e.g. Nie et al, 1995;van Oosten and Besford, 1995;van Oosten et al, 1995;Pearson and Brooks, 1995;Usuda and Shimogawara, 1998). For this reason, I examined the photosynthetic capacity of the fi rst leaf of plants at various developmental stages under ambient and elevated CO 2 .…”
mentioning
confidence: 99%